2016
DOI: 10.2308/bria-51561
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Ethical Environments of CPAs: Public Accounting versus Industry

Abstract: The purpose of this paper is to investigate certified public accountants' (CPAs) perceptions of their ethical environments. More specifically, we compare the perceptions of CPAs in (1) public accounting firms to those in industry, and (2) perceptions of CPAs at Big 4 public accounting firms to those at non-Big 4 firms. The ethical environment is one component of overall organizational culture and is important for encouraging ethical decision making. Based on responses from 904 CPAs, we find CPAs working at pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
2
22
0
8
Order By: Relevance
“…When we asked why the questionable inflation of company revenues or delay of revenue recognition might occur, the regulators indicated that they believe it is pressure from management, linked to short term goals as stated by Interviewee 9 -Accountant: "pressure from managers is one of the factors that forced accountants to practice accounting manipulation." Organizations that are more embodied in short-term profit-maximization, tend to be associated with weaker ethical environments (Bobek et al, 2016).…”
Section: Pressures Onmentioning
confidence: 99%
“…When we asked why the questionable inflation of company revenues or delay of revenue recognition might occur, the regulators indicated that they believe it is pressure from management, linked to short term goals as stated by Interviewee 9 -Accountant: "pressure from managers is one of the factors that forced accountants to practice accounting manipulation." Organizations that are more embodied in short-term profit-maximization, tend to be associated with weaker ethical environments (Bobek et al, 2016).…”
Section: Pressures Onmentioning
confidence: 99%
“…Table 2 Panel A presents two studies in our sample investigating factors associated with such differences among auditors. Bobek et al (2017) find that the scale elements form a single factor, implying that multiple EMs jointly contribute to ethical culture. They also find stronger perceptions of ethical culture in Big 4 than in non-Big 4 firms.…”
Section: Perceptions Of Ethical Culturementioning
confidence: 88%
“…Consistent with prior research (Bobek et al , 2017; Buchheit et al , 2016), gender was included as a control variable given the potential effect on participants’ perceptions of AWAs, potential gender bias and measures of performance. See Table 1 for gender statistics.…”
Section: Methodsmentioning
confidence: 99%